Uma análise do discurso "revolucionário" em pichações - Knetsch, Patricia Castello Bucioli [UNIFESP] (2019)
This research proposes an analysis of revolutionary discourse in graffiti which theme is a female subject. The general objective of this work is to demonstrate that the chosen statements have contradictory characteristics: in the discursive practice the graffiti has revolutionary attributes, however, the dynamics of its semantic formation manifest conservative characteristics. The following question emerged: is graffiti, as far as the meaning it mobilizes, effectively subversive, or is there space for conservatism? This research has its theoretical basis in the theories of Michel Pêcheux, Jean-Jacques Courtine, Michel Foucault and Roland Barthes. From this point of view, graffiti as a revolutionary practice operates at the same time with conservative ideological values that mythify the female figure. Such values can be systematized in three pre-existing myths: (i) every woman is / should be a mother; (ii) every woman is / should be beautiful; (iii) every woman is / should be seduced. The statements analyzed are, from this point of view, divided between contravention and conservatism. Courtine describes divided statement as a disagreement among several positions of subjects over the same discursive formation. In this sense, the subject inscribed in the graffiti is divided between the myth of motherhood, beauty, and seduction that subjectivate the feminine figure from a conservative discourse, and affirmation of a modern feminine figure coming from a "revolutionary" discourse.